EMERGÊNCIA E CRESCIMENTO INICIAL DO AMENDOIM SUBMETIDO AO ESTRESSE POR ENCHARCAMENTO - SILVA, Bruno da Costa; OLIVEIRA, Camilla Paulino de; DOURADINHO, Gabriel Zanuto; BORTOLAZZO, Guilherme; ZOZ, Tiago (ANAIS DO ENIC, 2018)
-